Investigation of Consultations Requested by Dermatology Inpatient - Dağdaş AD; Fettahlioglu Karaman B; Aksungur VL (Clinical, Cosmetic and Investigational Dermatology)
Ahmet Doğukan Dağdaş, Bilge Fettahlioglu Karaman, Varol Lütfü Aksungur Department of Dermatology, Çukurova University, Faculty of Medicine, Adana, TurkeyCorrespondence: Ahmet Doğukan Dağdaş, Cukurova University, Faculty of Medicine, Department of Dermatology, Adana, 01330, Turkey, Tel +90 506 8326195, Fax +90 322 3387144, Email dogukan1993@hotmail.comBackground: Although dedicated dermatology wards have been closed in some countries, they continue to exist in others. Inpatient consultations requested from dermatologists have been investigated widely. However, those requested by dermatologists have been taken into consideration only in a few studies.Objective: This study aimed to investigate such consultations, particularly in the context of diagnoses, reasons, and consulting specialties.Methods: Patients admitted to the dermatology ward of a tertiary hospital in Turkey between January 2019 and August 2021 were retrospectively analyzed.Results: The most common diagnoses were non-pustular psoriasis (11.5%), pruritus (10.9%), and urticaria (10.6%) in 548 admissions with a median length of stay of 15.1 days. There were 1712 consultations. Their number per admission was positively correlated with patient’s age and length of stay. Highest numbers were observed in admissions with a diagnosis of bullous pemphigoid, leg ulcers, lupus erythematosus, pustular psoriasis, hidradenitis suppurativa, and pemphigus. Reasons for consultation were management of comorbidity (53.8%), evaluation for drug precaution (19.1%), investigation for etiology (12.8%), evaluation for systemic involvement (6.0%), taking treatment advice (5.4%), obtaining biopsy (3.0%), and differential diagnosis (1.9%).Conclusion: Our findings showed that the number of consultations per admission was high, and the most common reason for consultation was comorbidity, indicating that, practically, there are no more pure dermatological patients. Therefore, if dedicated dermatology wards will continue to exist, in order to lower the number of consultations so length of stay, dermatologist should be trained in a manner so that they have more knowledge about common comorbidities.Keywords: inpatient dermatology, consultation, ward, length of stay, comorbidity